University Teachers and Students’ Preparedness and Management of Online Learning in COVID-19 Pandemic (Comparative & International Education Series, 2022)
This chapter examines university and students’ preparedness for and management of online learning during the COVID-19 pandemic in Nepal. We report on the processes of technical preparation, managing challenges, and creating an e-learning atmosphere at the university. We utilized semi-structured interviews and observations to gather qualitative data. We report on how university teachers and students, particularly in urban areas, struggled with limited information and communication technology (ICT) infrastructure, weak administrative support, lack of training, and poor internet connectivity to manage their online learning. An alternative learning mode, online learning enabled students to explore their self-learning strategies and work on their knowledge from home in their flexible time. Many rural students could not access online education due to a lack of digital devices and the Internet. Developing basic ICT infrastructure, adequate budget allocation, and extensive training for teachers would support creating an effective online teaching and learning atmosphere in higher education institutions.How to cite in APA:Baral, R. P., & Rana, K. (2022). University teachers and students’ preparedness and management of online learning in COVID-19 pandemic. In E. J. Valeau, R. L. Raby, & U. Gaulee (eds), Shaping a humane world through global higher education: Pre-challenges and post-opportunities during a pandemic (pp. 91-104). STAR Scholars.